HUBUNGAN SIKAP EMPATI DENGAN PERILAKU SOSIAL REMAJA DI PESANTREN ZAKIYUN NAJAH TAHAN AJARAN 2024/2025 - Devita Elina Harahap; Nurul Azmi Saragi; Nur Asyah; Ika Sandra Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between empathy and social behavior of adolescents at the Zakiyun Najah Islamic Boarding School in the 2024/2025 Academic Year. The background of this study is based on the importance of empathy as an emotional aspect that can influence the way adolescents interact socially, especially in an Islamic boarding school environment that is full of values of togetherness and caring. This study uses a quantitative approach with a correlational method. The sample in this study was 32 students who were taken randomly from grades VII to XI. The instruments used were an empathy attitude questionnaire and a social behavior questionnaire that had been tested for validity and reliability. The validity test showed that 33 items from each questionnaire were declared valid. The reliability test showed a Cronbach's Alpha value of 0.9165 for empathy and 0.942 for social behavior, which means that both instruments are very reliable. The results of the normality test showed that the data were normally distributed with a significance value of 0.200. The linearity test showed that the relationship between the two variables was linear with a significance value of 0.775. Hypothesis testing using Pearson correlation analysis shows a positive and significant relationship between empathy and adolescent social behavior, with a correlation value of 0.576 and a significance of 0.001 (p < 0.05). This shows that the higher the empathy of adolescents, the better their social behavior